Disease and the Hippo Pathway: Cellular and Molecular Mechanisms - Hansen, Carsten Gram (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Hippo pathway is a highly dynamic cellular signaling nexus that plays central roles in multiple cell types and regulates regeneration, metabolism, and development. The Hippo pathway integrates mechanotransduction, cell polarity, inflammation, and numerous types of paracrine signaling. If not tightly regulated, dysregulated Hippo pathway signaling drives the onset and progression of a range of diseases, including fibrosis and cancer. The molecular understanding of the Hippo pathway is rapidly evolving. This Special Issue contains ten articles contributed by established and up-and-coming Hippo pathway experts that, as a whole, provides an up-to-date overview of how dysregulated Hippo pathway activity is a common driver of specific diseases. The articles have a particular focus on the underlying molecular and cellular mechanisms that cause the Hippo pathway to go awry, and especially how this drives disease. The articles analyze disease-specific as well as common themes, which provides valuable insights into the fundamental molecular mechanisms in the dysfunctioning Hippo pathway, and thereby offer practical insights into potential future therapeutic intervention strategies.